Socioeconomic Inequity in Access to Medical and Long-Term Care Among Older People - Shohei Okamoto; Atsuhiro Yamada; Erika Kobayashi; Jersey Liang (International Journal for Equity in Health)
Abstract Background Ensuring equitable access to medical and long-term care (LTC) is critical to enable older people to maintain their health and well-being even after they undergo a decline in their intrinsic capacity. Methods We used data from five waves of the National Survey of the Japanese Elderly, conducted between 2002 and 2021, to assess gradients in access to medical care and LTC by income and education among Japanese individuals aged 60 years and above. Specifically, we assessed self-reported unmet needs for medical care and LTC, and public LTC use, and estimated the concentration indices (CI) to evaluate the degree of inequality and inequity. We standardised public LTC use by need and non-need variables. We analysed data derived from up to 1,775 person-wave observations from 1,370 individuals. Findings The pooled incidence across waves of forgone medical care, self-reported unmet support for activities of daily living (ADL) or instrumental ADL (IADL), and those not certified for LTC services even with ADL or IADL limitations were 4.6%, 15.5%, and 62.5%, respectively. Public LTC use demonstrated pro-higher education and pro-rich distribution, whereas the gaps decreased for need-predicted use. Based on the CI estimates, no explicit inequality was found for forgone medical care. However, we observed inequity in standardised LTC use across education, indicating pro-higher education inequality, particularly among women and those aged ≥ 80 years. Conclusion Improving the understanding of available resources and strengthening the functions of health centres and communities are required to detect the needs of citizens and facilitate their access to necessary care.